Duration of deafness impacts auditory performance after cochlear implantation: A meta‐analysis - Bernhard, Nikolai (Laryngoscope Investig Otolaryngol, 2021)
OBJECTIVE: Hearing loss is a highly disabling condition. Cochlear implantation is an established remedy if conventional hearing aids have failed to alleviate the level of disability. Unfortunately, cochlear implant (CI) performance varies dramatically. This study aims to examine the effects of duration of deafness (DoD) prior to cochlear implantation and the postoperative duration of implant experience with resulting hearing performance in postlingually deaf patients. METHODS: A systematic literature review and two meta‐analyses were conducted using the search terms cochlear implant AND duration deafness. Included studies evaluate the correlation between the DoD and auditory performance after cochlear implantation using monosyllabic and sentence tests. Correlation coefficients were determined using Pearson's correlation and Spearman rho. RESULTS: A total of 36 studies were identified and included data on cochlear implantations following postlingual deafness and postoperative speech testing of hearing outcomes for 1802 patients. The mean age ranged from 44 to 68 years with a DoD of 0.1 to 77 years. Cochlear implant use varied from 3 months to 14 years of age. Speech perception, which was assessed by sentence and monosyllabic word perception, was negatively correlated with DoD. Subgroup analyses revealed worse outcomes for longer DoD and shorter postoperative follow‐up. CONCLUSION: DoD is one of the most important factors to predict speech perception after cochlear implantation in postlingually deaf patients. The meta‐analyses revealed a negative correlation between length of auditory deprivation and postoperative sentence and monosyllabic speech perception. Longer DoD seems to lead to worse CI performance, whereas more experience with CI mitigates the effect.